Diálogos y transversalidades en la enseñanza literaria (El Hilo de la Fabula, 2020)
This article presents an overview of the teaching of literature in secondary education in Argentina over the last thirty years, referring to the fields of teaching, training, curriculum management and research. Within this framework, it ruminates on the analysis of an instrument generated by the Ministry of Education of Argentina between 2013 and 2015 that allowed observing the changes in policies regarding the object of literature as an object of teaching and the incidenceof technologies and the policies of digital inclusion on this school discipline of secondary education.
Keywords: Secondary education; Literature; Teaching; Multimodality